Revolutionizing Education with Artificial Intelligence (AI)? Challenges, and Implications for Open and Distance Learning (ODL) - Mohd Rushidi Mohd Amin; Ismaanzira Ismail; Vinesh Maran Sivakumaran (Social Sciences and Humanities Open)
Artificial Intelligence (AI) has rapidly progressed in recent years, profoundly impacting various industries. One sector significantly influenced by AI is education, notably Open and Distance Learning (ODL). This transformative technology holds the potential to revolutionize education delivery through personalized learning algorithms, adaptive learning, and intelligent tutoring systems, tailoring educational experiences to individual students. Real-time feedback and customized learning pathways, adapting to students' abilities and preferences, are among the capabilities AI brings to the educational landscape. However, as AI integration in ODL becomes more pervasive, it raises critical privacy concerns such as data collection and storage, user consent and control, data security and confidentiality, ethical standpoint and consideration, third-party services and integrations, and compliance with regulations. While recognizing the potential benefits of AI in education, it is essential to acknowledge and address the challenges associated with these privacy concerns. By exploring these facets, educators, policymakers, and researchers gain valuable insights into mitigating risks and ensuring responsible AI deployment in ODL. This paper highlights the importance of keeping current with the latest AI advancements in quality education. It provides a comprehensive view of AI's benefits, challenges, and potential in ODL. Lastly, this paper advocates for a balanced approach that harnesses the transformative potential of AI while safeguarding the privacy and ethical considerations vital for maintaining the integrity of education systems.